2020
DOI: 10.1139/apnm-2018-0849
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid is a key player in salt-induced endothelial dysfunction: the therapeutic role ofStigma maydis(corn silk) extract

Abstract: Hyperuricemia has been implicated in the pathogenesis and complications of cardiovascular diseases with associated elevated oxidant events. There is evidence that excessive salt intake results in cardiometabolic disturbances but the mechanism is elusive. Also, Stigma maydis (corn silk) is noted for its antioxidant properties among other beneficial roles. This study, therefore, aimed to establish the effect of high-salt diet (SD) on uric acid (UA) production and the role of S. maydis in salt-induced phenotypes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…One of the possible mechanism might be uric acid deposition on the blood vessels walls activates the renin-angiotensin system, suppress the liberate of carbon monoxide, enhance inflammation, and leads to vasoconstriction later [ 62 ]. Another possibility involving oxidative stress and endothelial dysfunction related with high SUA level may contribute to elevated blood pressure [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible mechanism might be uric acid deposition on the blood vessels walls activates the renin-angiotensin system, suppress the liberate of carbon monoxide, enhance inflammation, and leads to vasoconstriction later [ 62 ]. Another possibility involving oxidative stress and endothelial dysfunction related with high SUA level may contribute to elevated blood pressure [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…e keywords "hyperuricemia" and "gout" were entered into the TTD, Drugbank, Dis-GeNET, Genecards, OMIM, and PharmGkb databases to obtain gout-related targets. e numbers of disease-related targets were 20, 66, 258, 2319, 13, and 4, respectively, and after deduplication were 20,38,234,1971,13, and 4, respectively. A total of 2081 targets were obtained.…”
Section: Disease Targets Of Goutmentioning
confidence: 99%
“…Based on the syndrome, different methods, such as the promotion of blood circulation, diuresis, and invigorating the kidney, are adopted [11]. rough syndrome differentiation, effective Chinese medicines for gout treatment have been discovered, such as turmeric [12], corn silk [13], and tuckahoe [14]. Both clinical applications and modern pharmacological research have confirmed the uric acidlowering effect of these herbs.…”
Section: Introductionmentioning
confidence: 99%
“…Определение содержания оксида азота, супероксиддисмутазы, глутатионпероксидазы и мочевой кислоты в крови и сосудистых тканях лабораторных животных позволило подтвердить существенные негативные изменения, произошедшие под влиянием повышенного потребления соли. Наряду с этим, авторами исследования отмечено, что, благодаря своим антиоксидантным свойствам, терапевтический потенциал экстракта КСР может быть востребован при окислительном повреждении, вызванном высоким содержанием соли и/или мочевой кислоты [30].…”
Section: диуретическое и нефропротекторное действиеunclassified